I-03 Dysregulation of T helper-type cytokines and interferons appear during early systemic lupus erythematosus pathogenesis and contribute to clinical disease development. (31st August 2016) - Munroe, Melissa E; Lu, Rufei; Slight-Webb, Samantha R; Guthridge, Joel M; Niewold, Timothy B; Tsokos, George C; Keith, Michael P; Harley, John B; James, Judith A
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disease stemming from a poorly understood preclinical stage of autoantibody and symptom accrual. Antinuclear autoantibodies (ANAs) accumulate during this preclinical period. As many healthy individuals are also ANA-positive, this study aimed to identify further immune dysregulation that may contribute to disease pathogenesis. Materials and methods: SLE-associated autoantibodies, serum IFN-alpha activity and soluble mediators from multiple immune pathways were measured in serial serum samples from the Department of Defense Serum Repository by bead-based assays and cell-based reporter assays. Eighty-four patients with samples available pre- and post-SLE classification (average timespan = 5.98 years) were compared to 86 matched healthy controls. Temporal and predictive connexions between autoantibodies, soluble mediators, and SLE classification were determined by mixed linear regression, growth curve modelling, path analysis, analysis of covariance and random forest analyses. Results: In cases, but not matched controls, autoantibody specificities and IFN-associated mediators accumulated over a period of years, plateauing near the time of disease classification ( p < 0.001 ). Nine soluble mediators, including IL-5 (q = 4.35 × 10 −6 ) and IL-6 (q = 8.26 × 10 −6 ), were significantly elevated in cases vs. controls >3.5 years pre-classification. Th1 -type, Th17 -type, and TNF superfamily soluble mediators increased longitudinally in cases approaching SLE classification, but not in controls (q < 0.05). In particular, levels of BLyS and APRIL were comparable in cases and controls until <10 months pre-classification (q = 0.003 and q = 0.019, respectively). During the early preclinical stage, random forest models incorporating IL-5 and IL-6 levels (79–82% accuracy) distinguished future SLE patients better than models with ANA alone (58% accuracy). Autoantibody positivity coincided with or followed type II IFN dysregulation, preceding IFN-α activity in growth curve models, with elevated IFN-α activity and BLyS levels occurring shortly before SLE classification ( p ≤ 0.005 ). Cases were distinguished by multivariate random forest models incorporating IFN-γ, MCP-3, anti-chromatin and anti-spliceosome antibodies (accuracy 93% >4 years pre-classification; 97% within 2 years of SLE classification). Conclusions: Years before SLE classification, enhancement of the type II IFN pathway allows for accumulation of autoantibodies and subsequent elevations in IFN-α activity immediately precede SLE classification. These and other serologic mediators demonstrate a long progression of immune dysregulation leading to SLE classification. Immunological profiles that distinguish individuals who develop clinical SLE may be useful for delineating early pathogenesis, discovering therapeutic targets, and designing prevention trials. Acknowledgements: This study was supported by funding from the National Institutes of Health, including the National Institute of Allergy, Immunology, and Infectious Diseases, Office of Research on Women's Health, National Institute of General Medical Sciences, and National Institute of Arthritis, Musculoskeletal and Skin Diseases, and the US Department of Veterans Affairs. The views and conclusions contained herein are the views of the authors and do not necessarily represent the official views of the Departments of the Army, Navy, or Defense, the Department of Veterans Affairs, or the NIH.